Targeted therapy for metastatic colorectal cancer. Issue 10 (3rd October 2018) - Price, Timothy J.; Tang, Monica; Gibbs, Peter; Haller, Daniel G.; Peeters, Marc; Arnold, Dirk; Segelov, Eva; Roy, Amitesh; Tebbutt, Niall; Pavlakis, Nick; Karapetis, Chris; Burge, Matthew; et al.
ABSTRACT: Introduction : Outcomes in metastatic colorectal cancer are improving, with better understanding and use of targeted therapies. Areas covered : A review of the literature and recent conference presentations was undertaken on the topic of systemic treatment of metastatic colorectal cancer. This article reviews the current evidence for targeted therapies in advanced colorectal cancer, including up-to-date data regarding anti-epidermal growth factor receptor (EGFR) and anti-vascular endothelial growth factor (VEGF) agents, the relevance of primary tumor location and novel subgroups such as BRAF mutated, HER2 amplified, and mismatch-repair-deficient cancers. Expert commentary : EGFR-targeted and VEGF-targeted antibodies are now routinely incorporated into treatment strategies for metastatic colorectal cancer (mCRC). The use of EGFR-targeted antibodies should be restricted to patients with extended RAS wild-type profiles, and there is evidence that they should be further restricted to patients with left-sided tumors. Clinically, mCRC can be divided into subgroups based on RAS, BRAF, HER2, and MMR status, each of which have distinct treatment pathways.